Prevention Strategy for Human Trafficking in the Issuance Process of The Republic of Indonesia Passport for Prospective Indonesian Migrant Workers - Atika Ariyani Saraswati (Eduvest - Journal of Universal Studies, 2024)
The rapid development of technology in the current era is also utilized in creating environmentally friendly products, amidst the industrial world that is beginning to have social and environmental impacts, which can influence lifestyle and societal behavior, influenced by factors such as economic ability, awareness, and the abundance of goods proportional to the increasing needs of individuals, where appearance is a very important factor to be considered to enhance beauty. With increasingly fierce competition, the Somethinc brand creates quality and environmentally friendly beauty products while still considering the impact on the environment in the future. To address this challenge, this study aims to investigate the factors influencing the purchase intention of Somethinc products. Research data were obtained through an online survey involving 200 respondents. Data analysis was conducted using Structural Equation Model (SEM) with the SmartPLS 4 analysis tool. The results show that Product Innovation does not affect purchase intention, while green marketing and brand awareness influence purchase intention. Brand image mediates the influence of product innovation, green marketing, and brand awareness on purchase intention for Somethinc products among Generation Z in Indonesia.